2018
DOI: 10.1088/1758-5090/aae5fe
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of microscale vascularized fat that responds to perfusion with lipoactive hormones

Abstract: Current methods to treat large soft-tissue defects mainly rely on autologous transfer of adipocutaneous flaps, a method that is often limited by donor site availability. Engineered vascularized adipose tissues can potentially be a viable and readily accessible substitute to autologous flaps. In this study, we engineered a small-scale adipose tissue with pre-patterned vasculature that enables immediate perfusion. Vessels formed after one day of perfusion and displayed barrier function after three days of perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…In vitro microvascular systems have significant potential in three main areas, as highlighted in the excellent review in Reference 89: therapeutic vascularization of damaged tissue, vascularizing engineered tissues to create better implants (90), and microphysiological systems. In vitro microvascular systems that do not use blood have made enormous contributions to our…”
Section: Minding the Gap: Bridging Engineering And Microvascular Researchmentioning
confidence: 99%
“…In vitro microvascular systems have significant potential in three main areas, as highlighted in the excellent review in Reference 89: therapeutic vascularization of damaged tissue, vascularizing engineered tissues to create better implants (90), and microphysiological systems. In vitro microvascular systems that do not use blood have made enormous contributions to our…”
Section: Minding the Gap: Bridging Engineering And Microvascular Researchmentioning
confidence: 99%
“…Solute permeability tends to be comparable to those of explanted microvessels and up to an order-of-magnitude higher than those observed in vivo. Vessels in these gels can also be used to perfuse microscale biomaterials and tissues (64,246,340). Skin equivalents that incorporate vessels can be used to study vascular absorption of topically applied substances (390).…”
Section: Decellularization Of Organsmentioning
confidence: 99%
“…Skin equivalents that incorporate vessels can be used to study vascular absorption of topically applied substances (390). The addition of adipocytes to the gel increased vascular permeability (340).…”
Section: Decellularization Of Organsmentioning
confidence: 99%
“…Then hydrogel was added into the reservoir and the stainless‐steel needle was pulled out after the gel was set. The PDMS‐based chip allowed robust perfusion of supplied nutrition in the casted hydrogel . Li et al demonstrated the engineering of a vascularized adipose tissue by casting collagen gel with adipocytes in the reservoir and vascularizing the channel with ECs.…”
Section: Engineering Approaches On Fabricating Perfusable Microchannementioning
confidence: 99%
“…Li et al demonstrated the engineering of a vascularized adipose tissue by casting collagen gel with adipocytes in the reservoir and vascularizing the channel with ECs. With the constant and robust perfusion, the adipose tissue could be remained viable and respond to hormone stimuluses with lipid accumulation or loss . Mannino et al modeled a complex tumor microenvironment by constructing a perfusable and vascularized lumen within the hyaluronic acid‐based hydrogel.…”
Section: Engineering Approaches On Fabricating Perfusable Microchannementioning
confidence: 99%